Combined D2‐/L2‐hydroxyglutaric aciduria (SLC25A1 deficiency): clinical course and effects of citrate treatment. Issue 5 (1st April 2014) - Mühlhausen, Chris; Salomons, Gajja S.; Lukacs, Zoltan; Struys, Eduard A.; van der Knaap, Marjo S.; Ullrich, Kurt; Santer, René
Abstract: Combined D, L‐2‐hydroxyglutaric aciduria (DL‐2HGA; OMIM #615182) is a rare neurometabolic disorder clinically characterized by muscular hypotonia, severe neurodevelopmental dysfunction, and intractable seizures associated with respiratory distress. Biochemically, DL‐2HGA patients excrete increased amounts of D‐ and L‐2‐hydroxyglutarate (D2HG and L2HG, respectively), with predominance of D2HG, and α‐ketoglutarate, and show a decrease in urinary citrate. Impaired function of the mitochondrial citrate carrier (CIC) due to pathogenic mutations within the SLC25A1 gene has been identified as the underlying molecular cause of the disease. CIC mediates efflux of the mitochondrial tricarboxylic acid (TCA) cycle intermediates citrate and isocitrate in exchange for cytosolic malate. Thus, depletion of cytosolic citrate as well as accumulation of citrate inside mitochondria have been considered to play a role in the pathophysiology of DL‐2HGA. Here, we report for the first time on a patient with a genetically confirmed diagnosis of DL‐2HGA and treatment with either malate or citrate. During malate treatment, urinary malate concentration increased, but beyond that, neither biochemical nor clinical alterations were observed. In contrast, treatment with citrate led to an increased urinary excretion of TCA cycle intermediates malate and succinate, and by trend to an increased concentration of urinary citrate. Furthermore, excretion of D2HG and L2HG was reduced during citrate treatment. Clinically, the patient showed stabilization with regard to frequency and severity of seizures. Treating DL‐2HGA with citrate should be considered in other DL‐2HGA patients, and its effects should be studied systematically.